Critical analysis on the use of cholecalciferol as a COVID-19 intervention: a narrative review - Chagas, Stephanye Carolyne Christino (2021)
BACKGROUND: The World Health Organization has declared that a pandemic situation exists in relation to the disease caused by the new coronavirus, COVID-19. So far, the absence of a vaccine against the new coronavirus has led people worldwide to seek various therapeutic alternatives, including use of cholecalciferol. DESIGN AND SETTING: Narrative review developed by a research group at a public university in Recife (PE), Brazil. METHODS: We searched the literature on the use of cholecalciferol for prevention or treatment of COVID-19, using the MEDLINE and LILACS databases, with the keywords “vitamin D”, “cholecalciferol”, “SARS-CoV-2”, “COVID-19” and “coronavirus”, from January 1, 2020, to June 10, 2020. Narrative reviews, cohort studies and ecological studies were selected. RESULTS: We retrieved 32 references, of which 8 were considered eligible for intensive review and critical analysis. These comprised five narrative reviews, two observational studies and one protocol proposal. Most of the studies selected reported positive effects from use of vitamin D for prevention or treatment of COVID-19. However, there was little quantitative data to assess the real impact of using this vitamin as an intervention against this disease. CONCLUSIONS: Current studies on vitamin D used for purposes other than bone health promotion cannot be taken as support to justify its use in a disease as recent as COVID-19. Studies of greater robustness, with higher levels of clinical evidence, need to be conducted. Rational use of this vitamin needs to be ensured, thereby minimizing the impacts on the patient and the public healthcare system.